2023
DOI: 10.1590/1517-8692202329012022_0376
|View full text |Cite
|
Sign up to set email alerts
|

Core Training in Martial Arts Athletes

Abstract: Introduction: Martial arts comprise skill-based fighting games whose early specialized training is essential for development. Martial arts techniques are based on body movements requiring physical coordination, body stability, and endurance. Objective: Design a specific training for the abdominal center in martial arts athletes. Methods: Twelve martial arts athletes were selected as research subjects. These athletes were submitted to experimental training for six semesters. According to the characteristics o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
0
0
Order By: Relevance
“…The relevance of core training extends to several athletic performance variables, including, but not limited to, standing long jump and rebound jump. Li & Du (2023) conducted an elaborate study on martial arts athletes, employing a randomized controlled trial design. They found that core strength exercises, particularly planking and rotational movements, significantly improved the core muscle stability of the participants.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The relevance of core training extends to several athletic performance variables, including, but not limited to, standing long jump and rebound jump. Li & Du (2023) conducted an elaborate study on martial arts athletes, employing a randomized controlled trial design. They found that core strength exercises, particularly planking and rotational movements, significantly improved the core muscle stability of the participants.…”
Section: Literature Reviewmentioning
confidence: 99%